KONTRIBUSI DAN DAMPAK SOCIAL-AWARENESS TERHADAP GROUP PERFORMANCE MELALUI PEMBELAJARAN KIMIA: QUANTITATIF APPROACH - Almubarak Almubarak (Universitas Lambung Mangkurat, 2017)
Abstract. This study aimed to know the impact and contribution of awareness to group performance in learning chemistry. The purposive sampling technique is the sampling technique used. Data analysis technique used is multiple linear regression, partial regression coefficient, and correlation. The samples used 43 chemistry students. Data collection techniques used observations, instruments of emotional intelligence and ECGN (Emotional Competence Group Norms). The results showed that except for X1, the constant value of regression increased by the value of X2-X5 variable that increased, it means that there was a slight increase. The t test shows that there is no impact of self awareness on group performance with points t h < t tb (-0.817 < 2.026), lack of contribution of variable X to Y with R Square value 8,1% (0,081), and sign> 0,05.Keyword: Self-Awareness, Group Performance, Learning Chemistry.